THORACIC ENDOMETRIOSIS — THE RARE PATHOLOGY IN THORACIC SURGERY - A. A. Pichurov; O. V. Orzheshkovskiy; I. V. Dvorakovskaya; L. A. Romanova; B. E. Ivanishchak; E. A. Karelskaya; A. M. Petrunkin; A. S. Petrov; M. A. Atyukov; P. K. Yablonskiy (Вестник хирургии имени И.И. Грекова)
Thoracic hematogenic endometriosis is a rare pathology. A clinical course hasn’t pathognomic symptoms, because of it, the diagnosis is established due to histological study. The article presented two cases of female patients, who were suffering from thoracic endometriosis. They were hospitalized to the department of thoracic surgery of Municipal multifield hospital № 2 in Saint-Petersburg. The first patient had a posterior mediastinum tumor with asymptomatic disease course. The second patient was with recurrent catamenial pneumothorax.